ANALISIS PENGARUH DISIPLIN KERJA DAN PELAYANAN APARATUR DESA TERHADAP KEPUASAN MASYARAKAT DESA BALA KECAMATAN WERA - Aryandi Aryandi; Jaenab Jaenab (Bajang Institute, 2022)
This study aims to determine the positive and significant effect of work discipline and work services of village officials on the satisfaction of the people of Bala Village, Wera District. The instrument in this study used a questionnaire with a Likert scale. The population in this study is the community of the village of Bala with a sampling technique with incidental sampling technique so the sample is 35 people who have visited the village of Bala for services. Data collection techniques using observation, interviews, questionnaires and documentation. The data analysis technique uses validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination, simultaneous test and partial test, using SPSS version 22 for windows. Based on the results of the partial test that 1) Work Discipline has a positive and significant effect on Community Satisfaction in Bala Village, Wera District. 2) Service of the Bala Village Apparatus has no positive and significant effect on Community Satisfaction in Bala Village, Wera District. Based on the results of the Simultaneous test that 3) Work Discipline and Village Apparatus Services simultaneously have a positive but not significant effect on Community Satisfaction in Bala Village, Wera District.